Elevated M-MDSCs in Circulation Are Indicative of Poor Prognosis in Diffuse Large B-Cell Lymphoma Patients - Wang, Zhitao (J Clin Med, 2021)
Myeloid-derived suppressor cells (MDSCs) are defined as negative regulators that suppress the immune response through a variety of mechanisms, which usually cluster in cancer, inflammation, and autoimmune diseases. This study aims to investigate the correlation between M-MDSCs and the clinical features of diffuse large B-cell lymphoma (DLBCL) patients, as well as the possible accumulation mechanism of M-MDSCs. The level of M-MDSCs is significantly increased in newly diagnosed and relapsed DLBCL patients. Regarding newly diagnosed DLBCL patients, the frequency of M-MDSCs is positively correlated with tumor progression and negatively correlated with overall survival (OS). More importantly, the level of M-MDSCs can be defined as a biomarker for a poor prognosis in DLBCL patients. Additionally, interleukin-35 (IL-35) mediates the accumulation of M-MDSCs in DLBCL patients. Anti-IL-35 treatment significantly reduces levels of M-MDSCs in Ly8 tumor-bearing mice. Thus, M-MDSCs are involved in the pathological process of DLBCL. Targeting M-MDSCs may be a promising therapeutic strategy for the treatment of DLBCL patients.